Bacillus subtilis biofilm extends Caenorhabditis elegans longevity through downregulation of the insulin-like signalling pathway - Verónica Donato (Nature Portfolio, 2017)
Probiotic bacteria can improve host health, but the mechanisms underlying such beneficial effects are often unclear. Here, the authors show that biofilm formation of the probiotic bacteriumB. subtilis extends the lifespan of its host, the nematode C. elegans, by reducing insulin-like signalling.